Task design for telecollaborative exchanges: In search of new criteria. (February 2017) - Kurek, Malgorzata; Müller-Hartmann, Andreas
Abstract: This study examines the relationship between the criteria used for task evaluation and the process of actual task design using an Exploratory Practice approach. A telecollaborative task-based teacher training course serves as a research environment in which German and Polish students collaborate online in international groups designing and evaluating tasks for prospective telecollaborative learners. Having analysed the processes of teacher trainees' task design and evaluation, the authors argue for more tightly structured telecollaboration tasks and for task sequences which are constructed to enable each task to build on the outcomes of the previous one. As the findings reveal, telecollaboration tasks should conform to pedagogic task-based criteria, rather than to the more open and SLA-oriented CALL task appropriateness criteria proposed in Chapelle (2001). The authors, guided by the analysis of teacher trainees' learner texts and reflections, propose a new set of such criteria to be implemented in telecollaborative task design.